Water and wastewater finance and pricing : the changing landscape - Raftelis, George A. (Boca Raton : CRC Press, Taylor & Francis Group, 2015)
'This new edition updates all areas covered in the previous editions, and expand topics to include: major trends in the water and wastewater finance and pricing; management structures supporting finance and pricing; water budget pricing; reuse water pricing; wholesale and wheeling rates; computer modeling of financial and pricing systems; finance and pricing management graphics and reports; risk management in establishing water and wastewater rates and selecting alternative delivery methods; overview of storm water finance, data management and pricing; and public education outreach.'--
'Preface For decades, we have taken great pride in having served an industry that has been committed to environmental protection and public health. During this period, the water and wastewater industry has been dynamic and rapidly evolving. Utilities have sought new and better ways to accomplish their mission of providing high-quality and responsive service to its customers, while being environmentally compliant and socially sensitive. Over the years, it has been an honor to assist our utility clients in developing and implementing effective financial, pricing, and management systems. As we have attempted to deliver high-quality services, we have looked to improve the way the industry addresses its financial and management challenges. With this objective in mind, we have captured much of what we have learned and developed over the years in the fourth edition of this book. The fourth edition goes well beyond the scope of the third edition as it tackles timely and important issues such as: - Discussing cutting-edge management approaches and initiatives, and the importance of strong financial management in addressing financial and pricing goals of the utility; - Expanding the discussion related to traditional financing options, to take into account: challenges that the current economic climate has posed for utilities; innovative approaches to financing; the roles of different participants in the financing process; and providing an overview of high-profile financings that the have been completed recently; - Including techniques for projecting demand by retail and wholesale customer classes, addressing declining per capita water consumption trends, and discussing the related risks associated with not meeting demand forecasts; -'--
Includes bibliographical references and index.
Keywords: Water-supply -- Finance; Water-supply -- Rates; Sewage disposal -- Finance; Sewage disposal -- Rates